WORK-FAMILY CONFLICT: IMPLICATION ON MENTAL WELL-BEING AMONG WORKING WOMEN - Salleh, Sakinah; Mohd Yunus, Alwi; Sulaiman Dorloh (AR-RĀ’IQ, 2023)
Building a good family structure is very important in the development of a country’s society. Today’s world is getting more challenging when working women must work to earn their living. This study through content analysis aims to present the implications of work-family conflict on working women’s mental health. It aims to investigate factors of work-family conflict among working women, the implications of work-family conflict among working women and possible solutions towards the work-life balance of working women. The study found that working women are often faced with conflict in balancing careers and families. Work-family conflict is a source of stress and has been linked to negative effects such as increased health risks, less effective parenting, decreased productivity, tardiness, absenteeism, poor attitudes and morale, reduced life satisfaction, and lower mental health. Therefore, it is very important for working women to know the methods and solutions that can be done to reduce the role conflict they face and get social support and find effective coping strategies that can increase their level of emotional well-being. Family support is essential for women to be able to perform tasks in a balanced way. Women also need the motivation to ensure the momentum to work with passion and dedication, and at the same time ensure good family management so that career and family can achieve balance.